Risk of childhood leukaemia and non-Hodgkin's lymphoma after parental occupational exposure to solvents and other agents: the SETIL Study. Issue 9 (1st June 2013) - Miligi, Lucia; Benvenuti, Alessandra; Mattioli, Stefano; Salvan, Alberto; Tozzi, Giulio Andrea; Ranucci, Alessandra; Legittimo, Patrizia; Rondelli, Roberto; Bisanti, Luigi; Zambon, Paola; Cannizzaro, Santina; Kirchmayer, Ursula; et al.
Abstract : Aim: In the context of the Italian Multicentric Epidemiological Study on Risk Factors for Childhood Leukaemia and Non-Hodgkin's Lymphoma (SETIL), the risk of childhood cancer was investigated in relation to parental occupational exposures. Methods: All cases of childhood leukaemia and non-Hodgkin's lymphoma (NHL) in children aged 0–10 years were identified. Controls were chosen at random from the local population in each region. Parents were interviewed using a structured questionnaire. The collected data were blindly reviewed by expert industrial hygienists in order to estimate exposure to a list of agents. Statistical analyses were performed for each agent using unconditional multivariable logistic regression models, taking into account timing of exposure. Results: 683 cases of acute childhood leukaemia, 97 cases of NHL and 1044 controls were identified. Increased risk of childhood leukaemia was found for maternal exposure to aliphatic (OR 4.3) or aromatic hydrocarbons (OR 3.8) in the preconception period, and for paternal exposure to diesel exhaust (OR 1.4), lead exposure (OR 1.4) and mineral oils (OR 1.7). Risk of NHL appeared to be related to paternal exposure to oxygenated solvents (OR 2.5) and petrol exhaust (OR 2.2). Conclusions: We found increased risk for childhood leukaemia associated with maternal occupational exposure to aromatic and aliphatic hydrocarbons, particularly in the preconception period; increased risks were also observed for paternal exposure to diesel exhaust fumes, mineral oils and lead. The risk of NHL appeared to be related to paternal exposure to oxygenated solvent and petrol exhausts.